2001
DOI: 10.1002/1096-9861(20010226)431:1<11::aid-cne1052>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of pituitary adenylate cyclase-activating polypeptide (PACAP) in the frog (Rana ridibunda) tadpole brain: Immunohistochemical localization and biochemical characterization

Abstract: The anatomic distribution and biochemical characteristics of the neuropeptide pituitary adenylate cyclase-activating polypeptide (PACAP) were investigated in the central nervous system of the frog, Rana ridibunda, during development. Three to four days after hatching, at stages IV-VII, PACAP-immunoreactive perikarya were detected in the dorsal thalamus within the anterior ventral area, and a few fibers were found in the medial pallium. Positive cell bodies were first observed in the hypothalamus at stages VIII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
3
8
0
Order By: Relevance
“…Comparison of the distribution of PACAP-immunoreactivity in tadpoles and adult frogs reveals that PACAP is transiently expressed in the caudal part of the medial pallium and in Purkinje cells (Mathieu et al, 2001;Yon et al, 1992). This observation suggests that, in these structures, PACAP may act as a neurotrophic factor, as previously demonstrated in mammals (Gonzalez et al, 1997;Vaudry et al, 1998;.…”
Section: Ontogenesis Of Pacap In the Brainsupporting
confidence: 66%
See 4 more Smart Citations
“…Comparison of the distribution of PACAP-immunoreactivity in tadpoles and adult frogs reveals that PACAP is transiently expressed in the caudal part of the medial pallium and in Purkinje cells (Mathieu et al, 2001;Yon et al, 1992). This observation suggests that, in these structures, PACAP may act as a neurotrophic factor, as previously demonstrated in mammals (Gonzalez et al, 1997;Vaudry et al, 1998;.…”
Section: Ontogenesis Of Pacap In the Brainsupporting
confidence: 66%
“…This observation suggests that PACAP may interact with the ANF neuronal system to modulate various functions such as heart rate and hydromineral homeostasis. The transient expression of PACAP in Purkinje cells of frog tadpoles (Mathieu et al, 2001), as previously shown in newborn rats (Nielsen et al, 1998;Skoglösa et al, 1999a), suggests that the peptide may be involved in the control of proliferation, differentiation, and/or migration of nerve cells during development. In support of this hypothesis, it has been shown that PACAP acts as a neurotrophic factor regulating multiplication of nerve cells, neurite outgrowth, and apoptosis in the developing rat brain (Gonzalez et al, 1997;Lu and DiCicco-Bloom, 1997;Lu et al, 1998;Vaudry et al, 1998;.…”
Section: Functions Of Pacap In Amphibians Effect On the Central Nervosupporting
confidence: 61%
See 3 more Smart Citations